Sensori-motor recovery in post-stroke shoulder pain: a correlation study - Mukherjee, Ushnish; Kundu, Sourav; Gulati, Rachit; Mandal, Pankaj Kumar (International Journal Of Community Medicine And Public Health, 2020)
Background: The prevalence of pain in affected shoulder among post-stroke patients ranges from 34% to 84%. Numerous theories exist to explain the patho-mechanics behind development of Post-stroke shoulder pain, but its relationship with the sensori-motor recovery of the affected limb is still controversial. This study was conducted to detect the correlation, if any, between post-stroke shoulder pain and sensori-motor recovery of the affected upper limb. Methods: This observational longitudinal study was conducted on 73 patients of both sexes within the age group of 45-65 years having presentation of post-stroke (duration<6weeks) shoulder pain. Pain intensity was recorded in numerical rating scale (NRS). Sensorimotor recovery of the affected limb was assessed by Fugl- Meyer assessment scale of upper extremity (FMA-UE). Data were collected at the baseline (visit1), at 6 weeks (visit 2), 12 weeks (visit 3) and at the end of the study i.e., 24 weeks (visit 4). Results: Statistically significant negative correlations were found between severity of pain (assessed with NRS) and sensory-motor recovery (assessed with FMA-UE) on each visit with correlation coefficients (Spearman rho, r) being r=-0.890, p=0.000 on visit1, r=-0.685, p=0.000 on visit2, r=-0.629, p=0.000 on visit3 and r=-0.458, p=0.000 on visit 4. Conclusions: Post-stroke shoulder pain plays a significant negative role in sensori-motor recovery of the affected upper limb requiring early intervention.